Adaptation of Murbei Plant of Cultures in Vitro of Peat Soil - Faradilla Faradilla; Sulfianto Alias; Arini Rajab (Center for Journal Management and Publication, 2018)
Silk Sarong Samarinda is a sarong typical samarinda made using imported silk thread from China. Quality mulberry plants are needed to support the cultivation of silkworms (sericulture). Quality mulberry plants are obtained by in vitro propagation techniques. The success of in vitro culture needs to be supported also by the growth medium suitable for acclimatization stage and plantlet growth. As the medium grows peat has several advantages that are light, water-binding power and high air, porous and can create a good environment for the development of plant roots. Acclimatization by using peat media done in glass house. This research uses Completely Randomized Design (RAL) method with 5 (five) kinds of growing media combined with manure, compost and charcoal husk and without fertilization as control. Peat soil media successfully used for the growth of mulberry acclimation. Of the 5 (five) growing media attempted, the best growth of mulberry plants is on peat-growing medium: manure: charcoal husk (1: 1: 1) until 12 weeks after planting (MST) the addition of the number of shoots, the addition of the number of leaves as well as to the growth of plant height where at that height mulberry plants ready to be planted in the field.